Emergency care practitioner students’ satisfaction with simulation across two universities in South Africa - Strachan, Helen (Division of Emergency Medicine, 2020)
Background Simulation learning is an educational strategy that has been used in South African Emergency Care Practitioner training for at least a decade. No authors had previously measured the satisfaction of South African ECP students with simulation learning.